Heart of practice : within the Workcenter of Jerzy Grotowski and Thomas Richards - Richards, Thomas, 1962- (Routledge, 2008)
'Heart of Practice' is a unique and invaluable insight into the workings of one of theatre's true pioneers, presented by his closest collaborator. This book charts the development of Grotowski's life's work through a decade of conversations with his apprentice, Thomas Richards.